Keanekaragaman Araceae di Hutan Kampung Bumi Sahaja Distrik Yapsi Kabupaten Jayapura - Linda Aprilia Yansip; Leonardo E. Aisoi; Edoward Krisson Raunsay (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Indonesia is a country with highly diverse flora, ranking second in the world for its megabiodiversity. Araceae is a group of monocotyledonous Angiosperms characterized by flowers arranged in a spadix surrounded by a spathe, with either unisexual or bisexual inflorescences. This study aims to examine the diversity, distribution patterns, and utilization of Araceae species in the Bumi Sahaja Village Forest, using purposive sampling techniques with station placements based on forest types. The research findings show that there are 668 Araceae individuals, divided into 13 species, with moderate diversity and an even distribution pattern. Schismatoglottis calyptrata has the highest importance value, which is 47.14. In conclusion, 13 species of Araceae have been identified, with moderate diversity at each station, even distribution patterns, and two Araceae species used as ornamental plants, namely Alocasia lauterbachiana and Monstera adansonii.